1997
DOI: 10.1021/bi962516u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Asn/His L166 on the Hydrogen-Bonding Pattern and Redox Potential of the Primary Donor of Purple Bacterial Reaction Centers

Abstract: The primary electron donor (P) of the photosynthetic reaction center (RC) from the purple bacterium Rhodobacter (Rb.) sphaeroides is constituted of two bacteriochlorophyll molecules in excitonic interaction. The C2 acetyl carbonyl group of one of the two bacteriochlorophyll molecules (PL), the one more closely associated with the L polypeptide subunit, is engaged in a hydrogen bond with histidine L168, while the other pi-conjugated carbonyl groups of P are free from such hydrogen-bonding interactions. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
(122 reference statements)
4
20
0
Order By: Relevance
“…A conserved water, which is symmetry-related to water C and is assigned as 'water D', is present in this region of the protein. This water and its possible interaction with Asn L166 was previously mentioned in Ivancich et al (1997). The protein environment of His L168 is similar to that of His M197, with a few important structural differences that should be noted.…”
Section: Comparison Of Through-bond Interactions Near His M197 and His L168supporting
confidence: 56%
“…A conserved water, which is symmetry-related to water C and is assigned as 'water D', is present in this region of the protein. This water and its possible interaction with Asn L166 was previously mentioned in Ivancich et al (1997). The protein environment of His L168 is similar to that of His M197, with a few important structural differences that should be noted.…”
Section: Comparison Of Through-bond Interactions Near His M197 and His L168supporting
confidence: 56%
“…To complete this analysis, Fig. 2D shows data for all other mutations that have been constructed in the environment of the P BChls and where Δ E m P/P + has been reported [11,12,18,25–30]. Taken together with the rest of the data in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, the midpoint potential of the special pair has been shifted over quite a range using site‐directed mutagenesis 15, 38–46. Our aim, through the simulation of the structure and ionization potential of the R‐26 wild type and 20 mutants of Rb.…”
Section: Our Research Programmentioning
confidence: 99%
“…It has been shown that the addition or loss of hydrogen bonds by introducing or replacing histidine, for example, into the vicinity of P changes not only the vibrational spectra 16, 18, 44 of the special pair, but also alters the midpoint potential by up to several hundred millivolts without altering the energy of the singlet excited state P* relative to the ground state 45, 47–49. Mutants constructed in order to determine secondary protein effects for residues that do not interact directly with the special pair. For example, the L166 series of mutants 40 have been designed to interact with the special pair indirectly by either enhancing or diminishing the effects of the primary residue (L168), which can form a hydrogen bond with the 2a‐acetyl oxygen of P L . Likewise, the M210 50 series of mutants were designed to either increase or decrease the electron transport properties between P and the neighboring accessory bacteriochlorophyll BPh L .…”
Section: Our Research Programmentioning
confidence: 99%
See 1 more Smart Citation